APPLICATION OF DIGITAL MARKETING STRATEGIES TO INCREASE SALES OF UMKM PRODUCTS GUIDED BY BUMDES KUJATI PERDANA IN KARANGJATI VILLAGE PANDAAN PASURUAN - Utama, Muhammad Luthfi Alif (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The aim of this research is to analyze the application of Digital Marketing strategies to increase sales of MSME products assisted by BUMDES Kujati Perdana in Karangjati Village, Pandaan Pasuruan District. Digital Marketing makes it easier for MSME to attract consumers and increase product sales. The obstacles experienced occurred because Human Resources were less competent in managing Digital Marketing.This study uses a qualitative method. The informants in this research are MSME business actors assisted by Bumdes Kujati Perdana. The research location chosen in this research is the Karangjati BUMDES Office Center, Pandaan Bypass, Karangjati Village, Pandaan Pasuruan District. In this research are Technical Triangulation and Source Triangulation. The research data obtained using this technique is through interviews, then observation and documentation. The results of this research are that Digital Marketing is able to increase sales of MSME products. Digital Marketing also helps MSME in online product sales transactions with consumers via social media and E-Platforms. commerce. Obstacles experienced by MSME business actorsFirst BUMDES Kujati development in Karangjati Village, Pandaan Pasuruan District, namely Human Resources are still less competent in using Digital Marketing. Apart from that, the inconsistency of Human Resources in managing Marketing Strategies through Digital Marketing is also an obstacle for MSME players to increase sales of MSME products. This obstacle occurs because MSME actors only focus on production and offline buying and selling systems.